Analisis Struktural dan Pandangan Dunia Pengarang dalam Cerkak Cobaning Asmara - Lestari, Dewi; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The problem discussed in this study is the structural cerkak Cobaning Asmara which aims to describe and explain the author's worldview regarding the existence of Poerwadhie and the concept of true love contained in the cerkak Cobaning Asmara. This research is an analytical research to examine the contents of the cerkak, the author's worldview, and the concept of true love from the cerkak by using a qualitative descriptive method through a sociological approach to literature. The script used to examine the content is the Cobaning Asmara cerkak. This analysis stage starts from the reading stage, document recording, to document analysis. Data analysis techniques used include data collection, data presentation, and conclusion. Data collection techniques using textual techniques (library). The results of the study show that the author's worldview in cerkak cobaning romance includes (1) the Javanese view related to oneself, (2) the Javanese view related to others, (3) the concept of true love. The results of this study are structural in the cerkak cobaning romance, namely: Theme, this cerkak takes the theme of the struggle of a Titinastiti and Poewardhie in going through various trials in their relationship to the point of being together following their love and ideals. Characters and characterizations, the main character in this novel is Poewardhie, and the characterizations are described physically and physically. Setting, this story takes place in Yogyakarta. The plot used is mixed, but it is more advanced with a third-person omniscient point of view. This cerkak mandate is to be diligent and serious in dealing with life, not to give up and be determined to do something.